A method for preparing NdFeB permanent magnet material

Through the method of fast melt quenching, grinding, cold pressing and low-temperature thermal deformation mold binding deformation, the problem of the traditional thermally deformed neodymium iron boron magnet expanding grain size at high temperatures is solved, and high coercive force is achieved at low temperatures Preparation of neodymium iron boron magnets, suitable for industrial production.

CN116682661BActive Publication Date: 2024-12-24YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310534619.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-12
Publication Date
2024-12-24
Estimated Expiration
2043-05-12

AI Technical Summary

Technical Problem

Traditional thermally deformed neodymium iron boron magnets lead to a larger grain size under high temperature and slow speed conditions, reducing coercive force, making it difficult to obtain fine grain size and good moldability at low temperatures.

Method used

The strips are prepared by the quick melt quenching method, ground into powder, cold press into blocks, and used a double-layer thermal deformation mold for strong binding deformation, and controlled deformation amount and temperature to be heated within a lower range (≤760℃). Deformation.

Benefits of technology

The good moldability and small grain size of neodymium iron boron magnets are achieved at lower temperatures, which improves the coercivity of the magnets and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116682661B_ABST
    Figure CN116682661B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a NdFeB permanent magnet material, comprising the following steps: preparing a master alloy; breaking the master alloy into blocks, and then preparing strips by a melt quenching method; grinding the strips to obtain a powder; cold-pressing the obtained powder into blocks; thermally deforming the blocks obtained by cold-pressing, wherein the mold used for thermal deformation includes an outer mold and an inner mold, the outer mold is made of stainless steel, and the inner mold is made of graphite; the outer mold and the inner mold are both hollow cylinders with openings at both ends, and the outer mold is sleeved on the outer side of the inner mold and is coaxial with the inner mold. The preparation method provided by the invention can obtain a thermally deformed NdFeB material with good formability at a relatively low deformation temperature. The method is crucial for obtaining thermally deformed NdFeB magnets with smaller grain sizes and improving the coercive force of such magnets. The method is simple, easy to implement, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent magnetic materials, and in particular to a method for preparing a neodymium iron boron permanent magnetic material. Background Art

[0002] NdFeB permanent magnet material is the permanent magnet material with the highest magnetic energy product at present, and is called the "king of permanent magnets". Its most common preparation method is sintering or thermal deformation. Among them, NdFeB prepared by sintering has a very high magnetic energy product, which is close to the theoretical value of the magnet, but it does not meet the higher coercive force required in practical applications. The NdFeB magnet obtained by thermal deformation can obtain a finer grain size, which is beneficial to improve the coercive force of the NdFeB magnet. However, traditional thermal deformation of NdFeB magnets uses a higher temperature and a slower deformation pressing speed, and is carried out under unrestrained conditions. Since NdFeB material is a brittle material, only high temperature and slow speed can ensure the formability of the magnet. However, high temperature and slow speed will lead to the growth of grain size, thereby reducing coercive force. To obtain a fine grain size, thermal deformation needs to occur at a lower temperature. Therefore, how to improve the formability of NdFeB permanent magnet materials during low-temperature thermal deformation is a problem that needs to be solved at present. Summary of the invention

[0003] In view of the above technical problems, the present invention provides a method for preparing a NdFeB permanent magnet material.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] The present invention provides a method for preparing a NdFeB permanent magnet material, comprising the following steps:

[0006] Step 1: preparing master alloy;

[0007] Step 2: The master alloy in step 1 is crushed into blocks, and then a strip is prepared by a melt rapid quenching method;

[0008] Step 3: Grind the strips obtained in step 2 to obtain powder;

[0009] Step 4: cold-press the powder obtained in step 3 into blocks;

[0010] Step 5: thermally deforming the block obtained by cold pressing in step 4;

[0011] Among them, the mold used for thermal deformation includes an outer mold and an inner mold, the outer mold is made of stainless steel, and the inner mold is made of graphite; the outer mold and the inner mold are both hollow cylinders with openings at both ends, and the outer mold is sleeved on the outside of the inner mold and is coaxial with the inner mold.

[0012] In the technical solution of the present invention, the hollow portion of the inner mold is used to accommodate the cold-pressed block obtained in step 3.

[0013] As a preferred embodiment, the thickness of the outer mold is 0.5 to 10 mm;

[0014] Preferably, the thickness of the inner mold is 0.5-1 mm.

[0015] As a preferred embodiment, the chemical composition of the NdFeB permanent magnet material includes Nd x Fe y B z , where x, y, and z are atomic percentages;

[0016] Preferably, x is 11.8 to 15 at%; y is 78 to 84.2 at%; z is 4 to 7 at%;

[0017] Preferably, it further comprises an additive element; the additive element is selected from at least one of Nb, Zr, Ti, Cu, Ga and Al;

[0018] Preferably, among the added elements, the added amount of a single element does not exceed 1 at % in terms of atomic percentage.

[0019] As a preferred embodiment, in step 1, the preparation of the master alloy is often carried out by vacuum melting.

[0020] As a preferred embodiment, in step 2, the quenching speed of the melt is 27 to 32 m / s;

[0021] Preferably, in step 2, the stripping temperature in the melt rapid quenching is 1250-1350° C. In the technical solution of the present invention, in step 2, the strip is an amorphous structure strip, a nanocrystalline structure strip, or an amorphous and nanocrystalline mixed structure strip;

[0022] Preferably, the strip has a thickness of 10 to 40 μm, and has no limitation on width or length.

[0023] As a preferred embodiment, in step 3, the grinding method is not particularly limited and can be manual grinding or ball milling. In order not to destroy the strip structure obtained in step 2, manual grinding is preferred. In the technical solution of the present invention, the grinding is performed until the particle size of the strip is ≤200 mesh.

[0024] As a preferred embodiment, in step 4, the density of the cold pressed blocks is ≥80%;

[0025] In some specific embodiments, when the powder is cold pressed into blocks using a cold pressing mold, the inner hole diameter of the mold can be selected to be 3 to 10 mm, and the thickness of the blocks obtained by cold pressing generally does not exceed 3 mm. The pressing temperature can be selected to be room temperature or at a certain temperature, and can be pressed in air or in an argon atmosphere.

[0026] As a preferred embodiment, in step 5, the deformation amount of the thermal deformation is 75% to 85%; in the technical solution of the present invention, the deformation amount refers to the percentage of the reduction in the height of the thermal deformation mold;

[0027] Preferably, the temperature of the thermal deformation is 600-760°C;

[0028] Preferably, the thermal deformation time is 1 to 5 minutes.

[0029] In another aspect, the present invention provides a NdFeB permanent magnet material obtained by the above preparation method.

[0030] The above technical scheme has the following advantages or beneficial effects: the preparation method provided by the present invention can obtain hot-deformed NdFeB materials with good formability at a relatively low deformation temperature. The preparation method provided by the present invention first prepares a magnetic metal strip by rapid quenching of a melt, then crushes the strip into powder, and after cold pressing it into a dense block, uses a double-layer structured hot deformation die to forcefully deform it, and controls the deformation amount by controlling the magnitude of the deformation force. The preparation method provided by the present invention can perform hot deformation on NdFeB at a relatively low temperature (≤760°C). This method is crucial for obtaining hot-deformed NdFeB magnets with smaller grain sizes and improving the coercive force of such magnets. The preparation method provided by the present invention is simple to operate, easy to implement, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the process of rapid quenching of the melt in step 1 of Example 1 of the present invention.

[0032] Figure 2 It is a schematic diagram of the grinding process of step 2 in Example 1 of the present invention.

[0033] Figure 3 It is a schematic diagram of the cold pressing process in step 3 of Example 1 of the present invention.

[0034] Figure 4 It is a schematic diagram of the thermal deformation mold in Example 1 of the present invention and the process of using the mold to perform strong constraint deformation.

[0035] Figure 5 This is a physical picture of the NdFeB permanent magnet material prepared in Example 1 of the present invention.

[0036] Figure 6 This is the XRD spectrum of the NdFeB permanent magnet material in Example 1 of the present invention.

[0037] Figure 7 It is the hysteresis loop of the easy magnetization and hard magnetization directions of the NdFeB permanent magnet material in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0039] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0040] Embodiment 1:

[0041] The preparation method of the NdFeB material in this embodiment is as follows:

[0042] Step 1: Use vacuum melting to obtain the master alloy, the alloy composition is Nd 13.5 Fe 80.5 B6;

[0043] Step 2: The master alloy is crushed into blocks, and then the alloy is made into strips by melt rapid quenching method, such as Figure 1 As shown, the specific operation is as follows: an alloy block 1 after the mother alloy is crushed is placed in a quartz tube 5 with a small hole at the lower end, the alloy block 1 is melted into an alloy liquid 6 under the heating of a high-frequency copper coil 2, and the alloy liquid 6 is blown onto a rapidly rotating copper roller 3 under the action of an argon gas 4 with a pressure difference, and an alloy strip 7 can be thrown out, wherein the rotation speed of the copper roller 3 is 28m / s, the diameter of the quartz tube 5 is 0.7mm, and the distance from the lower tube mouth of the quartz tube 5 to the copper roller 3 is 3mm. The prepared alloy strip 7 has a thickness of about 13μm, a width of about 1.5-1.6mm, and an amorphous structure;

[0044] Step 3: If Figure 2 As shown, the alloy strip 7 obtained in step 2 is placed in an agate mortar 8 for manual grinding to obtain magnetic powder 9, and the particle size of the magnetic powder obtained by grinding is less than 200 meshes;

[0045] Step 4: Figure 3As shown, the magnetic powder 9 obtained in step 3 is cold pressed into a block, specifically, the magnetic powder 9 obtained in step 3 is placed in a cold pressing mold 10, the diameter of the inner hole of the cold pressing mold 10 is 5 mm, a pressure rod column 11 is placed at the bottom of the inner hole of the mold, a gasket 12 is placed at the bottom of the mold, and then placed on a cemented carbide lower pressure head 13, a pressure rod 15 is installed, and a cemented carbide upper pressure head 14 is placed on the top of the pressure rod 15. The upper / lower cemented carbide pressure heads 13 and 14 are pressed together to perform block pressing, and the block 16 obtained by pressing has a thickness of 1 to 2 mm and a density of 80%;

[0046] Step 5: Figure 4 As shown, the cold-pressed block 16 obtained in step 4 is placed in a hot deformation mold 19; wherein the hot deformation mold 19 includes an inner mold 17 made of graphite and an outer mold 18 of stainless steel sleeved on the outside of the inner mold 17; the outer mold 18 and the inner mold 17 are both hollow cylinders with openings at both ends and are coaxial; the inner mold 17 has an inner diameter of 5 mm (consistent with the size of the cold-pressed block obtained in step 4) and an outer diameter of 6 mm; the inner diameter of the outer mold 18 is 6 mm, the outer diameter is 9 mm, and the hot deformation mold 19 is 8 mm high; the inner mold 17 and the outer mold 18 are in seamless contact; and then the hot deformation mold 19 containing the block is deformed on a deformation device, and the deformation pressure head 20 and the deformation pressure head 21 respectively generate relative extrusion pressures, the deformation temperature is 750°C, the deformation time is 2.5 min, and the deformation amount is 80%.

[0047] In this embodiment, the actual photo of the NdFeB material obtained after the above thermal deformation is as follows: Figure 5 As shown, the specific operation is: after using wire cutting to cut off the stainless steel mold around the sample, the sample in the middle can be taken out intact without cracks and delamination due to the separation effect of the graphite inner mold.

[0048] In this embodiment, a series of characterizations were performed on the NdFeB magnets obtained in the above steps. The prepared material has a strong NdFeB magnet texture. From the XRD spectrum of the obtained material ( Figure 6 ), the magnet has a very strong (001) preferred orientation, and thus has a large magnetic anisotropy. In this embodiment, the hysteresis loop measured by a standard measuring instrument (vibrating sample magnetometer) characterizes the magnetic properties of the NdFeB permanent magnet material. The results are as follows Figure 7 As shown. The horizontal axis is the magnetic field intensity, the vertical axis is the magnetization intensity, and the important magnetic parameters on the hysteresis loop are Ms point (magnetization intensity when the magnetic field is maximum), remanence (magnetization intensity remaining when the magnetic field drops to 0), coercive force (magnetic field intensity when the magnetization intensity drops to 0), and maximum magnetic energy product (the maximum value of the product of magnetic induction intensity and magnetic field intensity, magnetic induction intensity is equal to magnetic field intensity + magnetization intensity * 4π). From Figure 7 It can be seen that the NdFeB permanent magnet material prepared in this embodiment has good magnetic properties, and the magnetic energy product is 48MGOe ( Figure 7 ).

[0049] Comparative Example 1

[0050] This comparative example adopts the same method as Example 1 to prepare NdFeB material, except that the heat deformation mold used in step 5 of this comparative example does not have an inner mold, but is a hollow cylindrical mold made of stainless steel with an inner diameter of 6 mm and an outer diameter of 9 mm.

[0051] The NdFeB material prepared in this comparative example was subjected to thermal deformation and cut by wire cutting. After being cut by wire cutting, the middle sample adhered to the stainless steel mold. The stress brought by the stainless steel mold was transmitted to the sample, resulting in the presence of delamination and crack penetration in the sample. It was not possible to cut out a block sample, but only thin flakes of fine slag.

[0052] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a neodymium iron boron permanent magnet material, characterized in that: The following steps are involved: Step 1: preparing master alloy; Step 2: The master alloy in step 1 is crushed into blocks, and then a strip is prepared by a melt rapid quenching method; Step 3: Grind the strips obtained in step 2 to obtain powder; Step 4: cold-press the powder obtained in step 3 into blocks; Step 5: thermally deforming the block obtained by cold pressing in step 4; Among them, in step 1, the preparation of the master alloy is usually carried out by vacuum melting method; in step 4, the density of the cold pressed block is ≥80%; in step 5, the deformation amount of the thermal deformation is 75%~85%; the temperature of the thermal deformation is 600~760℃; the time of the thermal deformation is 1~5 min; the mold used for the thermal deformation includes an outer mold and an inner mold, the outer mold is made of stainless steel, and the inner mold is made of graphite; the outer mold and the inner mold are both hollow cylinders with openings at both ends, and the outer mold is sleeved on the outer side of the inner mold and is coaxial with the inner mold; the hollow part of the inner mold is used to accommodate the cold pressed block obtained in step 4; the thickness of the outer mold is 0.5~10 mm; the thickness of the inner mold is 0.5~1 mm; The chemical composition of the NdFeB permanent magnet material includes Nd x Fe y B z ,in, x , y , z is the atomic percentage; x 11.8~15at%; y 78~84.2 at% z 4~7 at%; The deformation amount refers to the percentage of reduction in mold height used in the thermal deformation.

2. The preparation method according to claim 1, characterized in that: The chemical composition of the NdFeB permanent magnet material also includes additive elements; the additive elements are selected from at least one of Nb, Zr, Ti, Cu, Ga and Al.

3. The preparation method according to claim 2, characterized in that: Among the added elements, the added amount of a single element shall not exceed 1 at% in terms of atomic percentage.

4. The preparation method according to claim 1, characterized in that: In step 2, the quenching speed in the melt quenching is 27-32 m / s.

5. The preparation method according to claim 1, characterized in that: In step 2, the stripping temperature in the melt rapid quenching is 1250-1350°C.

6. The preparation method according to claim 1, characterized in that: In step 2, the strip is an amorphous structure strip, a nanocrystalline structure strip, or an amorphous and nanocrystalline mixed structure strip.

7. The preparation method according to claim 1, characterized in that: The thickness of the strip is 10-40 μm.

8. The preparation method according to claim 1, characterized in that: In step 3, the grinding is performed until the particle size of the strip is ≤200 mesh.

9. The NdFeB permanent magnet material obtained by the preparation method according to any one of claims 1 to 8.